2020
DOI: 10.3390/ijms21103688
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Metabolism and Interaction with Food Components

Abstract: The human gut contains trillions of microbes that play a central role in host biology, including the provision of key nutrients from the diet. Food is a major source of precursors for metabolite production; in fact, diet modulates the gut microbiota (GM) as the nutrients, derived from dietary intake, reach the GM, affecting both the ecosystem and microbial metabolic profile. GM metabolic ability has an impact on human nutritional status from childhood. However, there is a wide variability of dietary patterns t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 151 publications
(167 reference statements)
0
68
0
2
Order By: Relevance
“…SCFAs, such as acetate, propionate, and butyrate, mainly in the lumen, are assumed to interact in terms of antioxidant activity, avoiding anti-inflammatory effects on the intestinal mucosa. Moreover, butyrate and propionate can regulate intestinal physiology and immune function, whereas acetate acts as a substrate for lipogenesis and gluconeogenesis [ 24 ]. Bacteroidetes and Firmicutes are the most abundant phyla in the human gut, with Bacteroidetes mainly producing acetate and propionate, while Firmicutes mostly produces butyrate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs, such as acetate, propionate, and butyrate, mainly in the lumen, are assumed to interact in terms of antioxidant activity, avoiding anti-inflammatory effects on the intestinal mucosa. Moreover, butyrate and propionate can regulate intestinal physiology and immune function, whereas acetate acts as a substrate for lipogenesis and gluconeogenesis [ 24 ]. Bacteroidetes and Firmicutes are the most abundant phyla in the human gut, with Bacteroidetes mainly producing acetate and propionate, while Firmicutes mostly produces butyrate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that individuals with ADHD—who have lower levels of inhibitory control—have different bacteria present in their gut compared to individuals without ADHD [ 54 , 55 ]. Since gut microbiota are in constant interplay with diet, it is possible that the gut microbiota moderate the effects of diet on the brain via the microbiota-gut-brain axis [ 11 , 12 ]. As gut microbiota composition differs between 3-year-old children [ 56 ], it may affect the way nutrition impacts brain development in individual children [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…One biological pathway hypothesized to be involved in the association between breastfeeding, diet and inhibitory control is the microbiota-gut-brain axis, which is a bidirectional communication route between bacteria in the gut and the brain [ 11 ]. Gut microbiota are in constant interplay with diet; thus it is possible that the gut microbiota moderate the effects of diet on the brain and potentially affect behavior [ 11 , 12 ]. As inhibitory control develops quickly early in life, early life nutrition might be especially important.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have no information about symptomatic or asymptomatic gastrointestinal disorders. Nutrition and especially protein intake have an influence on microbial metabolism [ 37 , 38 ] and have been associated with intra-patient variability, as described previously [ 39 ]. Although we have no data about nutrition and dietary intake in the 4C-study, we used Mediterranean residency as a surrogate parameter for nutrition.…”
Section: Discussionmentioning
confidence: 99%